Famous back home [compact disc] - Dickerson, Russell, 1987- (Triple Tigers, 2025)
Multiplatinum Nashville-based singer, songwriter, and multi-instrumentalist Russell Dickerson has established himself a prolific songwriter and powerhouse showman through good old-fashioned performances and eloquent songcraft spiked with spirit.